Utilization of Human Virtual Intelligence Framework in Managing Technopreneur Knowledge - Yudha Pratomo (Generic, 2010)
This paper trying to discuss a framework to assist technopreneurs in managing knowledge. Using the concept of Human Virtual Intelligence, it is expected that the technopreneurs will be able to accelerate their abilities and competency to a desired level. Technopreneurs are mostly busy people with extreme time constraint. They do not have time and luxury to learn in the traditional way, but must go quickly to accommodate the chaotic changes and complex situations in their daily life. In such conditions, they must have a decision support system to help them do their daily strategic tasks. Knowledge Management System plays an important role to capture, share and exploit the knowledge from knowledge agents to the technopreneur’s Human Virtual Intelligence. This paper believes that using the Human Virtual Intelligence framework and Knowledge Management System will significantly help the development of technopreneurs.